2022
DOI: 10.1007/s10792-022-02480-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adverse events between intravitreal anti-VEGF and laser photocoagulation for treatment-requiring retinopathy of prematurity: a systematic review

Abstract: Purpose To synthesize existing evidence on adverse events, complications, and unfavorable outcomes of current treatment modalities for treatment-requiring retinopathy of prematurity (TR-ROP). Methods PubMed, Cochrane Central Register of Controlled Trials, Scopus, EMBASE, Trip Database, and the gray literature available were searched. Randomized Clinical Trials and observational studies comparing the adverse events of intravitreal anti-VEGF injections (beva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Retinal tissue ablation, visual eld reduction, and myopia occurrence are lower than laser photocoagulation. (5,14,(34)(35)(36) In our study, the incidence of severe ROP was 3.58 %. 19 patients received IVB injections and retinal vascularization was completed in all of them.…”
Section: Discussionmentioning
confidence: 74%
“…Retinal tissue ablation, visual eld reduction, and myopia occurrence are lower than laser photocoagulation. (5,14,(34)(35)(36) In our study, the incidence of severe ROP was 3.58 %. 19 patients received IVB injections and retinal vascularization was completed in all of them.…”
Section: Discussionmentioning
confidence: 74%
“…Laser treatment may be more efficacious in managing ROP with a significantly lower retreatment incidence than anti-VEGF treatment, and supplemental laser ablative treatment could reduce recurrence after initial anti-VEGF treatment [12,15]. However, myopia decreased significantly more with anti-VEGF treatment than with laser treatment [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…However, combined systematic reviews and meta-analyses, meta-analyses, or reviews [3,4,[10][11][12][13][14][15] comparing the laser-treated eyes with anti-VEGF monotherapy revealed that anti-VEGF injection caused less myopia, a lower prevalence of high myopia or astigmatism, and an overall lower risk of refractive errors in childhood. A subgroup analysis revealed a higher degree of myopia in aggressive posterior ROP than in type 1 ROP [11].…”
Section: Introductionmentioning
confidence: 99%
“…One systematic review published in 2022 concluded that more information is required concerning the adverse events, complications, and unfavourable functional and structural outcomes of the two treatment modalities in the long term. 12 In the interim analysis at 2 years of 180 infants in the RAINBOW trial, 13 as among 109 children at 2.5 years in the BEAT-ROP trial, 14 there was significant reduction of high myopia following anti-VEGF treatment compared to laser, but no visual acuity data have been published following a trial of anti-VEGF therapy for ROP.…”
Section: Introductionmentioning
confidence: 99%